Brain natriuretic peptide levels variation after left atrial appendage occlusion. Issue 1 (29th May 2015) - Cruz‐Gonzalez, Ignacio; Palazuelos Molinero, Jorge; Valenzuela, Maria; Rada, Ignacio; Perez‐Rivera, Jose Angel; Arribas Jimenez, Antonio; Gabella, Tania; Prieto, Ana Beatriz; Martín Polo, Jorge; Sánchez, Pedro L.
Abstract : Objective: To explore the variations of brain natriuretic peptide (BNP) secretion after left atrial appendage occlusion. Background: Left atrial appendage occlusion has been increasingly performed in the last few years, however little is known about the physiological consequences of left atrial appendage occlusion. Left atrial appendage regulates partially intravascular volume via release of brain natriuretic peptide. Brain natriuretic peptide levels have been related to increased risk of stroke in atrial fibrillation patients. Methods: Venous blood samples were obtained in consecutive patients undergoing left atrial appendage occlusion before, 24 hr after device implantation and at the first visit after discharge (45–60 days) for BNP measurement. Results: Left atrial appendage occlusion was performed in 34 patients with non‐valvular atrial fibrillation and contraindication to long‐term oral anticoagulation or at high‐risk of bleeding. There were no differences in BNP levels between baseline and 24 hr after device implantation. However left atrial appendage closure resulted in a significant decrease in BNP levels at the first follow‐up visit (45–60 days) compared to baseline measurements (759.90 pg ml −1 vs. 636.90 pg ml −1, P = 0.013). Conclusions: Left atrial appendage occlusion modifies BNP levels. These levels decrease after left atrial appendage occlusion. The clinical consequences of these findings need to be evaluated in further studies. © 2015 Wiley Periodicals, Inc.